PERBANDINGAN PEMIKIRAN DAN GERAKAN ANTARA KELOMPOK TALIBAN DI AFGHANISTAN DAN KELOMPOK FRONT PEMBELA ISLAM DI INDONESIA DALAM MEMPERJUANGKAN SYARIAT ISLAM - Mohamad Depara Pratama (2022)
The current occupation of Taliban has powerful implications serious about political dynamics in Afghanistan such as strengthening conservatism religion, violence, and nophobia in the last 10 years with the aim of adapting Afghan politics and society to Islamic law. Meanwhile in Indonesia, FPI has excellent human resources great in mobilizing the masses into their political movements and considered to have potential to carry out a similar movement with Taliban in fighting for Islamic law. In line with this, this research using descriptivequalitative method which tries to analyze How do Taliban and FPI have in common? is national in nature to fight for Islamic law in their country which certainly can affect the stability of national security. This research found that there are similarities in the mindset of Taliban and FPI regarding the establishment Islam, but FPI insists that FPI does not want to follow Taliban in apply Islamic law as in Afghanistan by means of violence and rebellion. FPI only wants to make Indonesia's sharia how to diplomacy with DPR and MPR so Islamic law is included in the Constitution. In line with this, this study uses a qualitative method descriptive research that tries to analyze how similar groups are Taliban and FPI which are both National fight for Islamic law in their country which of course can affect national security stability.